Student-Teachers’ Approaches to Learning, Academic Performance and Teaching Efficacy - Swee-Choo, Pauline Goh; Teck, Wong Kung; Osman, Rosma (Malaysian journal of learning & instruction, 2012)
Purpose – It is argued that the approaches to learning of students undergoing teacher training are likely to be related to their teaching and learning environment, especially as they move from a more regimented, structured learning environment in school to a tertiary learning environment that encourages more independent thinking and perhaps questions ideas. Therefore, this investigation has an overall goal to use the unique approaches to learning (surface and deep approaches) of students in a teacher preparation program to address the needs of this particular group of students during their teacher education. The study examines the associations between scores on student-teachers’ approaches to learning, their academic performance and teaching efficacy. Methodology – The approach to learning instrument used was the Bahasa Melayu R-SPQ-2F and the teaching efficacy was collected through the Bahasa Melayu Teachers’ Sense of  Efficacy Scale (TSES). The sample for this study was a total of 104 second-year student-teachers from two cohorts enrolled in a teacher education degree programme in a Malaysian university. The R-SPQ-2F was administered on the 10th week of a 14-week semester. A cover page accompanying the questionnaires provided general information about the study and specific instructions to answer the questionnaire. Student-teachers were requested to provide their cumulative grade point average (CGPA) score from the previous semester. Data was analyzed by using Pearson’s product-moment correlation coefficient (Pearson’s r). Findings - Findings showed that surface approach to learning has shown significant negative association with teaching efficacy, indicating that those student-teachers who used surface learning exhibited low teaching efficacy. Deep approach to learning has shown significant positive association with both academic achievement and teaching efficacy, indicating that those student-teachers who adopted deep learning had better academic achievement and also had a stronger sense of teaching efficacy. Implications of these findings were discussed as they related to teaching and learning, specifically in the attempt to facilitate deeper learning strategies. Significance - The study provides further evidence that the translated versions of the Bahasa Melayu R SPQ-2F and theBahasa Melayu TSES are reliable instruments to assess and monitor student-teachers’ approaches to learning and their teaching self-efficacy beliefs. This study also adds to the very limited number of investigations of approaches to learning, academic performance, and teaching self efficacy of student-teachers in Malaysia.